Pembuktian Tindak Pidana Mineral dan Batubara Dalam Putusan Bebas Ditinjau Dari Undang-Undang Nomor 8 Tahun 1981 tentang Hukum Acara Pidana (Studi Putusan Nomor 57/Pid.Sus/2023/PN Kba) - Wahyuni, Putri; Manik, Jeanne Darc Noviayanti; Toni, Toni (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
This research aims to find out and analyze the evidentiary system in Indonesia in terms of Law Number 8 of 1981 concerning criminal procedure based on the theory of evidence in mineral and coal crimes, and to know and analyze the evidentiary system in Indonesia viewed from theory of evidence in mineral and coal crimes, and to know and analyze the basis for the judge's consideration of the acquittal verdict. Analyze the basis of the judge's consideration of the acquittal decision. Type of research uses juridical-normative legal research, with qualitative analysis of legal materials. Analysis of legal materials qualitatively. The types and sources of legal materials in the research consist of the following types primary legal materials, secondary legal materials, and primary legal materials. Technique The technique of collecting legal materials is by library study techniques, obtained from secondary legal materials through the collection of legal materials and investigation of legal materials in the literature. Legal materials in the literature. The results of this study analyze the tool evidence on the theory of evidence and identify the advantages and disadvantages of the negative theory of evidence. theory of proof negatively. Understanding the judge's decision in making an acquittal verdict through a theoretical approach approach with the suitability of valid evidence and the judge's belief.